Open innovation : Factors explaining universities as service firm innovation sources - Janeiro, Pedro (2022)
The service innovation literature lacks empirical studies that focus on the links between service firms and universities. This paper aims to contribute to a better understanding of these links. This paper applies the Portuguese version of the Community Innovation Survey (CIS 2006) to obtain data on 967 service firms. The model uses a random intercept in an ordered probit regression to empirically assess which factors influence the collaboration of service firms with universities for innovation related activities. The regression also considers the unobserved firm heterogeneity. The results demonstrate that innovation success, radical innovations, and innovation intensity are crucial to the development of links between innovative service firms and universities.